A Carbon Nanoparticle Lymphatic Tracer Protected Parathyroid Glands During Radical Thyroidectomy for Papillary Thyroid Non-Microcarcinoma. (February 2017) - Long, Miaoyun; Luo, Dingyuan; Diao, Feiyu; Huang, Mingqing; Huang, Kai; Peng, Xinzhi; Lin, Shaojian; Li, Honghao
The study assessed the role of an activated carbon nanoparticle lymphatic tracer in reducing unintentional damage to the parathyroid glands during thyroidectomy for papillary thyroid non-microcarcinoma diagnosed intraoperatively by cryosections. A total of 103 patients with papillary thyroid non-microcarcinomas diagnosed by intraoperative cryosection were randomly assigned to receive routine radical thyroidectomy or radical thyroidectomy following administration of activated carbon nanoparticle lymphatic tracer to the contralateral thyroid, at the department of Thyroid Surgery, Sun Yat-sen Memorial Hospital (Guangzhou, China), between January 2012 and May 2013. The success of level VI lymphadenectomy and postoperative parathyroid function were compared. Administration of the activated carbon nanoparticle lymphatic tracer did not affect the frequency of recovered lymph nodes containing metastases; however, it did significantly reduce the incidence of permanent and transient hypoparathyroidism from 2 to 0 and 18 to 6, and reduced the mean recovery time for transient hypoparathyroidism from 57.0 days to 22.3 days. Administration of activated carbon nanoparticles to the contralateral thyroid after intraoperative cryosections did not contribute to lymphadenectomy for papillary thyroid non-microcarcinoma, but significantly protected parathyroid functions. This approach could decrease the morbidity of radical thyroidectomy and the occurrence of hypoparathyroidism.